Significant social inequalities exist between hot and cold extremes along urban-rural gradients. (July 2022) - Zeng, Peng; Sun, Fengyun; Liu, Yaoyi; Chen, Cheng; Tian, Tian; Dong, Qianqian; Che, Yue
Highlights: Exploring urban-rural social inequalities in cold exposure risk. Differences between social inequalities in exposure to hot and cold extremes. Heat and cold exposure risks show opposite urban-rural gradients. Low-educated people experience the most severe heat-related social inequalities. Children experience the most severe cold-related social inequalities. Abstract: Frequent weather extremes can exacerbate environmental injustices arising from the unequal distribution of public resources. To improve urban resilience, social inequality in exposure to heat wave events (HEs) is gradually attracting attention. However, few studies have focused on cold wave events (CEs), even though CEs can cause as much damage as HEs. Thus, a geographically weighted regression model is used to explore exposure inequalities among sensitive populations in CEs and urban-rural differences between social inequalities in exposure to HEs and CEs. Results show that children and ethnic minorities in low-urbanization areas and residents of vulnerable housing in high-urbanization areas are vulnerable to CEs. Females and drivers are vulnerable to CEs in all areas. However, inequality in HEs is most pronounced among the elderly, those with low levels of education, and outdoor workers. Exposure inequality increases with decreasing urbanization among the elderly, while the opposite is true for outdoor workers. Females are severely threatened by HEs in suburban and rural areas. Finally, we propose targeted recommendations based on the findings, such as strengthening medical coverage for empty nesters and introducing policies to safeguard cold work. We hope this study can provide a reference for guaranteeing equality in resilient urban planning.